Rice price policies in Indonesia: a computable general equilibrium (CGE) analysis - Robinson, Sherman; El-Said, Moataz; San, Nu Nu; Suryana, Achmad; Swastika, Dewa; Bahri, Sjaiful (International Food Policy Research Institute, 1997)
This paper presents an agriculture sector focused Computable General Equilibrium (AG-CGE) model for analyzing the economy-wide impacts of changes in technology, protection, and market structure on resource allocation, production, and trade in Indonesia. The paper incorporates a specification of the rice market and models the government price-support, stocking, and trade policies for rice using a mixed complementarity approach. This approach allows the specification of inequalities and changes in policy regime as prices and/or stocks move within specified bands. The model is used to examine the impact on the Indonesian economy of changes in rice yields given different assumptions about the operations of Bulog (National Logistic Agency). The general equilibrium approach captures and quantifies the effects of the price support policies on resource allocation, trade, relative prices, and the government budget. An important result is that there is inefficient allocation of resources within the agriculture sector and the rest of the economy if Bulog operates to maintain the rice price when there are significant increases in rice productivity. Instead of releasing resources to other high-value agriculture uses and non-agriculture uses, the price support scheme attracts more resources into rice production. In addition, the price support program is costly and strains the government accounts, even if the administrative costs of operating the program are ignored.